THE EFFECT OF FERTILIZER AND AGRICULTURAL MACHINERY SUBSIDIES ON PADDY PRODUCTIVITY: A FEASIBLE GENERALIZED LEAST SQUARES APPROACH - Priyanto, Moh. Wahyudi; Pratama, Adnan Putra; Prasada, Imade Yoga (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Paddy is a commodity that is widely cultivated by farmers in Indonesia. Paddy farmers are currently facing the threat of declining farm productivity due to land conversion activities, access to inputs that are difficult to reach, and climate change. However, productivity can be increased through the use of fertilizer inputs and agricultural machinery. Government support for paddy farmers is provided through input subsidies and agricultural machinery. Therefore, this study explores the effect of input subsidies and agricultural machinery on paddy productivity. We selected 20 provinces with the highest proportion of paddy fields to the total area. Feasible Generalized Least Squares (FGLS) analysis is used to determine the effect of subsidies on fertilizers and agricultural machinery on paddy productivity in Indonesia. The results showed that input subsidies were mostly allocated to Java, Sumatra, and Sulawesi islands, while agricultural machinery was allocated more to Sulawesi and Nusa Tenggara islands. FGLS analysis shows that the area of irrigated land, subsidies for urea fertilizer, subsidies for NPK fertilizers, subsidies for ZA fertilizers, and grants for 2-wheel tractors affect increasing paddy productivity. Meanwhile, the effect of increasing temperature causes a decrease in paddy productivity.